Impact of Awareness Campaign on the Knowledge of Risk Factors of HIV & AIDS among Students of University of Gujrat, Pakistan - Zahid Azam Chaudry , Ammara Khan , Shahzad Ali Khan , Zahid Azam Chaudry , Ammara Khan , Shahzad Ali Khan (Journal of Rawalpindi Medical College, 2019)
Background: Individuals of age 15-25 years are at highest risk of HIV/AIDS due to presence of high risk behavior. Public health professionals are of the view that educational intervention are more successful in improving knowledge attitudes and preventive practices among the young rather than abstinence only intervention. The aim of this study was to access the knowledge regarding HIV/AIDS of students of University of Gujrat, Gujrat and to find the effect of imparting education on these parameters. Methodology: pre-post quasi experimental study design conducted at University of Gujrat, Pakistan in the year 2015-2016. A sample size of 370 students was taken. A pre-structured self-administered questionnaire was used as a study tool, privacy and anonymity of the respondents were maintained. A comprehensive lecture and educational session was carried out that delivered information regarding HIV/AIDS disease nature, modes of transmission, myths associated with HIV/AIDS, and other disease facts. After an interval of three weeks the same questionnaire again got filled from the same students. The pre-intervention knowledge was compared to the post educational intervention one. Obtained data were evaluated by using SPSS version 20. Results were considered significant at p value of less than 0.05. Results: The student of UOG had fairly moderate knowledge of HIV/AIDS that was significantly modified (p≤0.01) after educational conditioning. And there was clear presence of will to disseminate HIV information, so that not only themselves but also their family member can be protected from this deadly infection. Conclusion: Educational intervention statistically significantly conditioned students knowledge of HIV/AIDS.